Тайна красного шатра: [для среднего школьного возраста] / Жанна Бочманова ; рисунки Дмитрия Никулушкина - Бочманова Жанна Юрьевна (Шляпа волшебника, 2018)
Экземпляры: ДБ (20201030) / Инвентарный номер: 53149 / Цена: 271.00 / Авт.знак: Б 86 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6